Dinamika Penggunaan Lahan dan Transformasi Perdesaan-Perkotaan di Wilayah Metropolitan Kedungsepur - Wardana, Ardiansyah Putra; Andrea Emma Pravitasari; Dyah Retno Panuju (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2026)
Urbanization represents a dominant worldwide phenomenon that increasingly transforms spatial system and ecological conditions across regions. The Kedungsepur Metropolitan area in Central Java Province, Indonesia, comprises Kendal, Demak, Ungaran (Semarang Regency), Semarang City, Salatiga, and Purwodadi (Grobogan) and represents one of the country’s rapidlydeveloping metropolitan regions. This metropolitan area provides a representative case for examining how urbanization shapes land use transitions, spatial clustering, and sustainability disparities within an underexplored integrative metropolitan perspective. This study aims to quantify land use and land cover (LUCC) change and assess rural-urban transformation. This study applies a gain-loss analysis to assess LULC dynamics, employs the rural urban index (RUI), uses spatial autocorrelation index (Moran’s I and Local Indicator for Spatial Association/LISA). Based on the LUCC analysis, extensive forest conversion to dryland agriculture and built-upareas occurred, totaling 64,739.09 ha, while the number of urban villages increased from 235 to 302 between 2012 and 2022. Kendal experienced the highest level of urban transformation (31%), whereas Salatiga and Grobogan showed minimal change (6%). A Moran’s I value of 0.83 indicates a strong spatial clustering of urban growth. The findings highlight the need of integrated spatial planning and strengthened urban-rural transformation as key strategies for achieve sustainable regional development.